2020
DOI: 10.1111/tbed.13769
|View full text |Cite
|
Sign up to set email alerts
|

An expert opinion assessment of blood‐feeding arthropods based on their capacity to transmit African swine fever virus in Metropolitan France

Abstract: To deal with the limited literature data on the vectorial capacity of blood-feeding arthropods (BFAs) and their role in the transmission of African swine fever virus (ASFV) in Metropolitan France, a dedicated working group of the French Agency for Food, Environmental and Occupational Health & Safety performed an expert knowledge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
13
0
2
Order By: Relevance
“…Ribeiro et al [83] showed that Ornithodoros erraticus sensu stricto ticks can become competent vectors when feeding on highly viremic pigs and on pigs with lower virus titres (i.e., animals with sub-acute and or chronic infection forms) [83]. Biting flies, such as Stomoxys calcitrans, may play a role in the spread of ASFV through their feeding cycle (via bites) [84,85] or by oral ingestion of infected flies [86,87]. ASFV was transmitted to susceptible pigs by S. calcitrans infected one hour and 24 h before, and the virus survived in those flies for at least two days without apparent loss of titre [84].…”
Section: Ticks and Other Blood Feeding Arthropodsmentioning
confidence: 99%
“…Ribeiro et al [83] showed that Ornithodoros erraticus sensu stricto ticks can become competent vectors when feeding on highly viremic pigs and on pigs with lower virus titres (i.e., animals with sub-acute and or chronic infection forms) [83]. Biting flies, such as Stomoxys calcitrans, may play a role in the spread of ASFV through their feeding cycle (via bites) [84,85] or by oral ingestion of infected flies [86,87]. ASFV was transmitted to susceptible pigs by S. calcitrans infected one hour and 24 h before, and the virus survived in those flies for at least two days without apparent loss of titre [84].…”
Section: Ticks and Other Blood Feeding Arthropodsmentioning
confidence: 99%
“…Вши вызывают педикулёз, вторичные бактериальные заражения в местах расчёсывания кожи, снижение иммунитета и аллергические реакции, а также являются переносчиками возбудителей опасных заболеваний человека -брюшного тифа (Salmonella enterica Le Minor et Popoff, 1987 var. typhi), сыпного тифа (Rickettsia prowazekii da Rocha-Lima, 1916), пятнистой лихорадки Скалистых Гор (R. rickettsi Brumpt, 1922), возвратного тифа (Borrelia recurrentis Bergey et al, 1925), Волынской или окопной лихорадки (Bartonella quintana Schmincke, 1917) [2] -и животных, например: свиная вошь (Haematopinus suis L., 1758) описана как вектор для поксвируса свиней (Chitovirales: Poxviridae, Suipoxvirus) [4] и вируса африканской чумы свиней (Asfuvirales: Asfiviridae, Asfivirus) [5] [16]. Много позже выясняется, что строгий физикоматематический анализ уравнений электростатики для диэлектриков представляет собой нетривиальную задачу [17; 18].…”
Section: ключевые словаunclassified
“…Несмотря на то, что представители отряда броненосцев имеют дорсальный кожный панцирь, с вентральной стороны их тело покрыто шерстью 5. Аналогичный эксперимент, более доступный в современных условиях, -это потереть пластмассовую ручку о волосы на голове 6.…”
unclassified
“…More recently, haematophagous flies have been also proposed as non-multiplying vectors for mechanical transmission of the ASF virus between porcine hosts Olesen, Lohse et al, 2018;Fila & Woźniakowski, 2020;Olesen et al, 2020;Saegerman et al, 2020;Vergne et al, 2020).…”
Section: Introductionmentioning
confidence: 99%